Pengaruh Faktor Keuangan dan Faktor Non Keuangan Terhadap Opini Audit Going Concern - Agustia Marshanda, Vera Tessa; Suci, Rama Gita; Fitriana, Nur (CV. ITTC INDONESIA, 2025)
The financial condition of a company can reveal its actual level of security, enabling users of financial statements to analyze its financial health and predict its future business continuity (going concern). This study aims to examine the effect of financial and non-financial factors on going concern audit opinions. This research is quantitative in nature. The population consists of 165 manufacturing companies listed on the Indonesia Stock Exchange (IDX). The sampling procedure employed purposive sampling, resulting in a final sample of 115 companies. The research variables include going concern audit opinion as the dependent variable and four independent variables: profitability, liquidity, audit tenure, and audit firm reputation. Data were collected through observation and documentation, using observation and documentation sheets as research instruments. Data analysis was conducted using multiple linear regression with SPSS 26. The findings indicate that profitability significantly influences going concern audit opinions. Liquidity, however, has no effect on going concern audit opinions. Meanwhile, audit tenure and audit firm reputation both have a significant effect on going concern audit opinions.